الهجرة غير الشرعية بين الشريعة والقانون - Tarek H. Aba Buamied
This study concentrates on illegal immigration issue from Sharia and law perspective. The objectives of this study are: to distinguish between legal and illegal immigration attitude, to highlight the legal description of illegal immigrants attitudes, to compare between the basis of forbidden illegal immigration and suit it by law and to illustrate the opinion of sharia law regarding illegal immigration comparing with other international and national laws. This study depends on the descriptive, comparative and analytical methods which lead to the following fading’s: the law development in both Libya and Tunis justice system accompanied this issue starting from individual cases to the organized plenty and suit. This study also discovers more key negative effect beside other negative effects regarding illegal immigration which is the security effect on the pass or targeted countries, in addition to the health effects as illegal immigrants contact with the citizens in pass or the targeted countries. Finally, the study reveal that Sharia doesn’t forbid the illegal immigration but the laid laws forbids it during the last few years from this century. This study suggests some recommendations to be taken which are: the importance of adjusting the illegal immigration laws in the Libyan and Tunis joint project to suit this phone mina.